Digital Scrapbook Development To Improve Literacy In Primary School Students - Iklimah, Siti Ema; Sofyan, Deddy; Yani, Indri (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2024)
The aim of this research is to determine the increase in elementary school students' literacy through the development of Digital Scrapbook teaching media in B.Indonesia lessons with Explanatory Text material. This research is based on the finding of a problem in elementary school that there is still a lack of use of technology in preparing media amidst increasingly rapid technological developments. The type of research used is Research and Development with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research subjects were fifth grade elementary school students. The feasibility of this teaching material is based on the results of validation tests by material experts, media experts, language experts, and student responses. And N-gain to calculate the effectiveness of reading literacy. The results of this research are the percentage of validation test scores by material experts with a score of 94% in the very feasible category, 91% for media experts in the very feasible category, and 90% for language experts in the very appropriate category. And based on the results of N gain, it was declared effective in increasing the reading literacy of elementary school students. Based on the results, it can be stated that the development of Digital Scrapbook learning media is valid and feasible and effective for increasing the reading literacy of students in elementary schools.